In Silico Analysis of the Metabolic Potential and Niche Specialization of Candidate Phylum "Latescibacteria" (WS3) - Youssef, Noha H. (PLoS One, 2015)
The “Latescibacteria” (formerly WS3), member of the Fibrobacteres–Chlorobi–Bacteroidetes (FCB) superphylum, represents a ubiquitous candidate phylum found in terrestrial, aquatic, and marine ecosystems. Recently, single-cell amplified genomes (SAGs) representing the “Latescibacteria” were obtained from the anoxic monimolimnion layers of Sakinaw Lake (British Columbia, Canada), and anoxic sediments of a coastal lagoon (Etoliko lagoon, Western Greece). Here, we present a detailed in-silico analysis of the four SAGs to gain some insights on their metabolic potential and apparent ecological roles. Metabolic reconstruction suggests an anaerobic fermentative mode of metabolism, as well as the capability to degrade multiple polysaccharides and glycoproteins that represent integral components of green (Charophyta and Chlorophyta) and brown (Phaeophycaea) algae cell walls (pectin, alginate, ulvan, fucan, hydroxyproline-rich glycoproteins), storage molecules (starch and trehalose), and extracellular polymeric substances (EPSs). The analyzed SAGs also encode dedicated transporters for the uptake of produced sugars and amino acids/oligopeptides, as well as an extensive machinery for the catabolism of all transported sugars, including the production of a bacterial microcompartment (BMC) to sequester propionaldehyde, a toxic intermediate produced during fucose and rhamnose metabolism. Finally, genes for the formation of gas vesicles, flagella, type IV pili, and oxidative stress response were found, features that could aid in cellular association with algal detritus. Collectively, these results indicate that the analyzed “Latescibacteria” mediate the turnover of multiple complex organic polymers of algal origin that reach deeper anoxic/microoxic habitats in lakes and lagoons. The implications of such process on our understanding of niche specialization in microbial communities mediating organic carbon turnover in stratified water bodies are discussed.